AI-Powered Meta-Analysis Automation - Muller, Lolita; Joshi, Namita; Steward, Peter Richard; Rosenstock, Todd Stuart (2025)
AI-Powered Meta-Analysis Automation accelerates evidence synthesis in agriculture by automating the repetitive stages of a review while preserving methodological rigor. The workflow covers: search-term generation, LLM-assisted screening, tagging, keyword extraction, classification, and harmonization. Outputs are systematically compared with expert manual reviews to quantify quality and relevance, clarifying where automation performs well and where caution is warranted.